2009
DOI: 10.1007/s10433-009-0126-8
|View full text |Cite
|
Sign up to set email alerts
|

Forgone health care due to cost among older adults in European countries and in Israel

Abstract: This study sought to identify the principal factors that predict forgone health care due to cost among European and Israeli older adults. The analysis applied the Andersen–Newman model of health service utilization to data from the first wave of the Survey of Health, Ageing and Retirement in Europe (n = 28,849). Relinquished health care was regressed on the predisposing characteristics, need factors and economic access attributes of the respondents, in general, and in each of 12 countries, in particular. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 40 publications
4
31
0
2
Order By: Relevance
“…We follow a similar approach. Their analysis showed that this variable was a main factor of reduced health care due to cost, revealing that financial uncertainty may lead to underutilisation of health services [29].…”
Section: Datamentioning
confidence: 99%
“…We follow a similar approach. Their analysis showed that this variable was a main factor of reduced health care due to cost, revealing that financial uncertainty may lead to underutilisation of health services [29].…”
Section: Datamentioning
confidence: 99%
“…The resulting pattern of what constitutes the most vulnerable groups remains remarkably robust. SUN is a more serious issue for the children of the poor (the reader is referred to a systematic review of the literature on children until 2006 [22] and some later studies [23][24][25][26][27][28][29]), for the homeless [30][31][32][33], for chronically ill patients [19,20,[34][35][36], for the disabled [21,37,38], for the sick and poor elderly [39][40][41][42] and for immigrants [43]. Extending insurance coverage for these groups or strengthening social protection measures (lowering OOP payments or increasing their income) should be an obvious target for any policy aiming at improving equity of access.…”
Section: Subjective Unmet Need and Out-of-pocket Paymentsmentioning
confidence: 99%
“…It operationalizes the decision to seek care as conditional upon predisposing factors underlying the propensity to use services (sociodemographic characteristics); enabling factors reflecting the ability to secure services (e.g., income, employment status, social support); and need indicating the illness level (e.g., symptom perception, self-perceived health, disease severity, chronic disease) (Andersen 1995). While this model has been used extensively in health services research, it has been largely neglected in cross-country settings, and when used, has often omitted important predisposing and enabling constructs (Evashwich et al 1984; Bird et al 2002; Fernandez-Mayoralas et al 2000; Litwin and Sapir 2009). …”
Section: Introductionmentioning
confidence: 99%